1984
DOI: 10.1128/aac.25.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of moxalactam in elderly subjects

Abstract: The pharmacokinetics of moxalactam were studied in 19 male volunteers 60 years of age or older with normal liver function tests and a creatinine clearance of 2 60 mlmin. Moxalactam was administered in single or multiple intravenous or intramuscular doses. Rapid and complete intramuscular bioavailability was demonstrated in a subgroup of the study population. The mean plasma half-life was 2.9 ± 0.8 h for intravenous doses and 3.5 ± 0.9 h for intramuscular doses. Average renal clearances of 0.04 liters/kg per h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Andritz et al (1984) also found that latamoxef plasma clearance showed a statistically significant correlation with creatinine clearance, but that the non-renal clearance was highly variable in subjects 60 years of age or older with normal liver function tests.…”
Section: Latamoxefmentioning
confidence: 91%
“…Andritz et al (1984) also found that latamoxef plasma clearance showed a statistically significant correlation with creatinine clearance, but that the non-renal clearance was highly variable in subjects 60 years of age or older with normal liver function tests.…”
Section: Latamoxefmentioning
confidence: 91%
“…Moxalactam pharmacokinetics in elderly subjects has been studied in 19 men aged 60–74 years 104 . The serum half‐life was slightly prolonged and drug clearance correlated with renal function; nonrenal elimination was highly variable.…”
Section: Pharmacology and Pharmacokinetics Of Antibioticsmentioning
confidence: 99%
“…Cephalosporin dosage regimens and serum half-lives (t'l2) in neonates, children and the elderly. Dosages listed do not reflect those for life-threatening infection or meningitis (data from Andritz et al 1984;Blouin et al 1989;Borin et al 1990;Faulkner et al 1988b;Hayton 1986;LeBel et al 1985;Meyers et al 1987Meyers et al , 1989Sugihara et al 1988 Nilsson-Ehle 1987; Meyers et al 1989;Montamat et al 1989). Pharmacokinetic studies of ceftazidime, ceftizoxime, and cefmenoxime conducted in elderly populations showed a doubling of tl/, by the age of 70, indicating the need for dosage reduction for these renally eliminated cephalosporins in this age group.…”
Section: Effect Of Agementioning
confidence: 99%